En introduktion til upernavikdialekten - Fortescue, Michael D. 1946- (1986)
Study of the eskimo dialect spoken in the Upernavik region of east Greenland focusing on the communities of Aappilattoq, Kullorsuaq, and Innaarsuit with the objective of determining from a compiled wordlist the similarities of the dialect to the east Greenland eskimo language.
Keywords: Kalâtdlisut dialect; Angmagssalik-Sprache; Mundart